Assessing composition gradients in multifilamentary superconductors by means of magnetometry methods. (18th November 2016) - Baumgartner, T; Hecher, J; Bernardi, J; Pfeiffer, S; Senatore, C; Eisterer, M
Abstract: We present two magnetometry-based methods suitable for assessing gradients in the critical temperature and hence the composition of multifilamentary superconductors: AC magnetometry and scanning Hall probe microscopy. The novelty of the former technique lies in the iterative evaluation procedure we developed, whereas the strength of the latter is the direct visualization of the temperature dependent penetration of a magnetic field into the superconductor. Using the example of a PIT Nb3 Sn wire, we demonstrate the application of these techniques, and compare the respective results to each other and to EDX measurements of the Sn distribution within the sub-elements of the wire.